Analisis Pemahaman Peserta Latsar CPNS terhadap Instrumen Analisis Isu: Pohon Masalah, Fishbone, dan SWOT - Diniyati, Nurul; Kurniadewi, Yogtavia Indah; Lestari, Restu; Rosmawati, Arvita (Jurnal Kridatama Sains dan Teknologi, 2025)
This study analyzes the level of understanding among participants in the Basic Training for BRIN Civil Servant Candidates (CPNS) regarding the use of issue-analysis instruments, namely Problem Tree, Fishbone, and SWOT. The research employed a mixed-methods approach with an Explanatory Sequential design, involving 19 participants from diverse scientific backgrounds and employment statuses. The findings indicate that participants demonstrated the highest initial understanding of the SWOT analysis (73.3%), whereas 62% showed limited understanding of the Problem Tree, and 57.1% had limited comprehension of the Fishbone method. No significant relationship was found between participants’ academic background or employment status and their level of understanding. SWOT was most frequently selected due to its simple structure, cross-context flexibility, and familiarity among participants. In contrast, comprehension of the Problem Tree and Fishbone was mainly achieved through experiential learning activities. The combination of SWOT and Problem Tree emerged as the most widely used because both methods complement one another in analyzing organizational issues at macro and micro levels. This combination enables participants to produce more comprehensive, focused, and relevant issue analyses to support policy alternative formulation. These findings underscore the importance of experiential learning approaches in civil service training to strengthen integrative and reflective policy-analysis competencies